Legal Protection for Victims of Sexual Violence in the Military Environment Through the Military Justice System - Pradana, Satur; Widijowati, Rr. Dijan (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2025)
This study examines the reporting mechanism and legal protection for TNI members who are victims of sexual violence in the military environment, and evaluates the extent to which military law has been responsive and accommodating to the case of Lieutenant AAP against seven private soldiers. Using normative legal research methods with a statutory, case, and conceptual approach, as well as descriptive qualitative data analysis, this study found that TNI members who are victims of sexual violence have several reporting channels, namely to their direct superiors/unit commanders, Provost/Military Police (POM), and the Internal Supervisory Agency (TNI Inspectorate/Forces). In terms of legal protection, Law Number 12 of 2022 concerning Criminal Acts of Sexual Violence (UU TPKS) and the Military Criminal Code (KUHPM) are the main comprehensive legal umbrellas. The KUHPM, both directly and through references to the general Criminal Code, provides a strong criminal basis. This study concludes that military law in Indonesia is fundamentally quite responsive and accommodating to handling sexual violence, in terms of the completeness of its regulatory instruments. There are multiple sanctions from the Criminal Code, the Military Disciplinary Law, and the Soldier's Code of Ethics.